Oxaspirol B with p97 Inhibitory Activity and Other Oxaspirols from Lecythophora sp. FL1375 and FL1031, Endolichenic Fungi Inhabiting Parmotrema tinctorum and Cladonia evansii - Wijeratne, E. M. Kithsiri; Gunaherath, G. M. Kamal B.; Chapla, Vanessa M. [UNESP]; Tillotson, Joseph; De La Cruz, Fabian; Kang, MinJing; U'Ren, Jana M.; Araujo, Angela R. [UNESP]; Arnold, A. Elizabeth; Chapman, Eli; Gunatilaka, A. A. Leslie (American Chemical Society (ACS), 2016)
A new metabolite, oxaspirol D (4), together with oxaspirols B (2) and C (3) were isolated from Lecythophora sp. FL1375, an endolichenic fungus isolated from Parmotrema tinctorum, whereas Lecythophora sp. FL1031 inhabiting the lichen Cladonia evansii afforded oxaspirols A (1), B (2), and C (3). Of these, oxaspirol B (2) showed moderate p97 ATPase inhibitory activity. A detailed characterization of all oxaspirols was undertaken because structures proposed for known oxaspirols have involved incomplete assignments of NMR spectroscopic data leading only to their planar structures. Thus, the naturally occurring isomeric mixture (2a and 2b) of oxaspirol B was separated as their diacetates (5a and 5b) and the structures and absolute configurations of 1, 2a, 2b, 3, and 4 were determined by the application of spectroscopic techniques including two-dimensional NMR and the modified Mosher's ester method. Oxaspirol B (2) and its diacetates 5a and 5b were evaluated for their ATPase inhibitory activities of p97, p97 mutants, and other ATP-utilizing enzymes, and only 2 was found to be active, indicating the requirement of some structural features in oxaspirols for their activity. Additional biochemical and cellular assays suggested that 2 was a reversible, non-ATP competitive, and specific inhibitor of p97.